Reclaiming Jakarta’s North Coast: Perspectives From The Defense, Security, And Constitutional Aspects - Setijawati, Vera Wheni (UI Scholars Hub, 2017)
Indonesia’s sea territory is particularly important in uniting the country, as the sea is a medium for interconnectivity; a medium for national integrity; a medium for resources; a medium for diplomacy; and a medium for national defense and security. This paper will focus on the sea’s significance to Indonesia’s national unity in its role as a medium for interconnecting the country’s many islands, and the implications thereof to Indonesia’s national security and defense. This paper will within this context discuss in particular the reclamation of Jakarta’s north coast. This research applies a normative empirical methodology, and intends to provide a scientific basis for the argument that as Jakarta’s coastline is crucial in terms of national defense and security matters, the coastline should therefore be managed by a state agency and remain publicly accessible.